2019
DOI: 10.1155/2019/2618307
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Nanothermometry Based on Pr3+ : LaF3 Single Core and Pr3+ : LaF3/LaF3 Core/Shell Nanoparticles

Abstract: Core Pr3+ : LaF3 (CPr = 1%) plate-like nanoparticles (nanoplates), core/shell Pr3+ : LaF3 (CPr = 1%)/LaF3 nanoplates, core Pr3+ : LaF3 (CPr = 1%) sphere-like nanoparticles (nanospheres), and core/shell Pr3+ : LaF3 (CPr = 1%)/LaF3 nanospheres were synthesized via the coprecipitation method of synthesis. The nanoparticles (NPs) were characterized by means of transmission electron microscopy, X-ray diffraction, and optical spectroscopy. The formation of the shell was proved by detecting the increase in physical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In general, information about the thermometric performance (thermal sensitivity, S r ) of the upconverting nanosensors is inferred from the fluorescence intensity ratio (Δ) of thermally coupled energy levels of the Ln 3+ ions. Several studies have reported that the thermometric parameter Δ, appears to be reliant on the type of host, type of dopant ion and their concentrations, , size of the nanoparticles, , surface functionalization, core–shell structure, , incorporation of transition metals, laser excitation density, and modification of the energy transfer processes (Table ). As such, detailed studies involving optimization of the chemical and spectroscopic properties of UCNP-based sensors have been performed to increase the operating temperature sensitivity and temperature resolution to fulfill the specific needs of given applications.…”
Section: Introductionmentioning
confidence: 99%
“…In general, information about the thermometric performance (thermal sensitivity, S r ) of the upconverting nanosensors is inferred from the fluorescence intensity ratio (Δ) of thermally coupled energy levels of the Ln 3+ ions. Several studies have reported that the thermometric parameter Δ, appears to be reliant on the type of host, type of dopant ion and their concentrations, , size of the nanoparticles, , surface functionalization, core–shell structure, , incorporation of transition metals, laser excitation density, and modification of the energy transfer processes (Table ). As such, detailed studies involving optimization of the chemical and spectroscopic properties of UCNP-based sensors have been performed to increase the operating temperature sensitivity and temperature resolution to fulfill the specific needs of given applications.…”
Section: Introductionmentioning
confidence: 99%